Co-cultivation of Rhodotorula glutinis and Chlorella pyrenoidosa to improve nutrient removal and protein content by their synergistic relationship. Issue 25 (7th May 2019) - Li, Huankai; Zhong, Yuming; Lu, Qian; Zhang, Xin; Wang, Qin; Liu, Huifan; Diao, Zenghui; Yao, Chuang; Liu, Hui
Abstract : Aiming at treating piggery wastewater and producing useful products, a novel method using a co-culture of Chlorella pyrenoidosa and Rhodotorula glutinis in piggery wastewater was proposed in this study to improve nutrient removal and the protein content in the feed produced. Abstract : With the continuous development of the livestock breeding industry, the amount of piggery wastewater discharged increases year by year, and the pressure of controlling environmental pollution continuously increases. A novel method using a co-culture of Chlorella pyrenoidosa and Rhodotorula glutinis in piggery wastewater was proposed in this study, which was aimed at treating piggery wastewater and producing useful products. The results showed that the optimal inoculum ratio of algae to yeast was 3 : 1 in the wastewater, which achieved the removal efficiencies of 58.53%, 36.07%, 33.20% and 56.25% for ammoniacal nitrogen (NH3 -N), total nitrogen (TN), total protein (TP) and chemical oxygen demand (COD), respectively, after 6 d. The synergistic relationship of C. pyrenoidosa and R. glutinis was preliminarily validated using the oxygen/carbon dioxide exchange balance and scanning electron microscopy images. The co-cultivation system gained 59.8% (w/w) protein within 5 d which can be used as a feed additive, and produces aquatic animals with better growth and quality. Thus, the 1000 litre pilot scale bioreactor was used indoors and removed 82.65% of TN, 53.51% of TP, 93.48% of NH3 -N and 85.44% of COD in 21 d which gave a better performance for TN ( p < 0.05) than the bench scale results. This system improves the nutrition removal and protein production efficiencies, and is a promising method for piggery wastewater treatment and the pig breeding industry.